A new species of Anacroneuria Klapálek 1909 (Plecoptera: Perlidae) from Espírito Santo State, southeastern Brazil and comments on additional species - Novaes, Marcos Carneiro; Bispo, Pitágoras Da Conceição; Gonçalves, Maísa De Carvalho (Zootaxa, 2016)
Specimens of Perlidae (Plecoptera) from Espírito Santo State in southeastern Brazil were studied. A new species, Anacroneuria ruschii n. sp. is described. Brief remarks on A. debilis (Pictet) and Kempnyia neotropica (Jacobson & Bianchi) are also presented.